Analysis of Occupational Safety and Health using The HAZOP Method on PT. ABC 3 Kg Lpg Gas Cylinder Maintenance Workshop Employees - SUHRA, AMINATUS (Universitas Trunojoyo Madura, 2023)
Every company activity is inseparable from the risk of danger, therefore companies need to make efforts to minimize the consequences that could be detrimental. To minimize this, risk management activities are needed. In risk management, we must know what potential dangers may occur in the activity and the level of risk posed so that we can take appropriate preventive and control measures. Potential hazard analysis was carried out at the 3kg LPG gas cylinder maintenance workshop at PT. A B C. Due to the production process activities carried out by the workers, the workers still lack the self-awareness to wear personal protective equipment and there are less ergonomic working postures. Analysis using the HAZOP Worksheet method. The results of data processing show that sources of danger that can or have the potential to cause work accidents are worker attitudes, work environment conditions, falling materials, noise and sand particles. It is known that there are ergonomic risks in the work of the 3KG LPG gas cylinder maintenance workshop. The risks experienced include musculoskeletal disorders and fatigue that appears in the waist, arms, wrists, calves and ankles, as well as the neck. General steps that can be implemented to reduce potential hazards and risks are to require and emphasize all workers to use Personal Protective Equipment and provide workers with the tools they need, such as ergonomic tables and chairs. By implementing this, it can reduce work-related accidents